Compare the Complications of Laparoscopic versus Open Appendectomy (Medical Forum Monthly, 2024)
Objective: To compare the complications of laparoscopic versus open appendectomy.Study Design: Retrospective studyPlace and Duration of Study: This study was conducted at Dow University Hospital from June 2012 to June 2014. Methodology: Data was analyzed by reviewing patient records, patients bills records and patient discharge sheet. Each data was double checked and thoroughly supervised by author himself to assure quality and validation of the data collected. The information reviewed of patients with diagnosis of acute appendicitis included, age , sex, time taken for bowel function restoration, use of analgesia, postoperative stay and its clinical evaluation and confirmed by USG of abdomen requiring operation and total charges. Patients included who were operated in surgical unit I. Patients who were identified with associated gynecological disease, to be at high risk for general anaesthesia, had a past history of lower abdominal surgeries, appendicular abscess were excluded.Data was analyzed through SPSS software.Results: 73 patients who underwent appendicectomy. Out of which 24(32.87%) patients operated laparoscopically and 49(67.12%) patients by open method. The mean age for open appendectomy was 26.53 ± 12.3 years whereas, for laparoscopic appendectomy it was 29.9 ± 13.3 years. Intraoperative findings were normal appendix 4(16.66%) in OA group and 2(4.08%) in LA group, Acute appendicitis 12(50 %) in OA group and 31(63.26%) in LA group, Gangrenous appendicitis 3(12.5%) in OA group and (14.28%) in LA group, Appendiceal abscess 4(16.66%) in OA group and 5(10.20%) in LA group, Peritonitis 1(4.16%) in OA group and 3(6.12%) in LA group. Post operative complications were observed in both groups. Wound infection 5(20.83%) in OA group and 2(4.08%) in LA group, Intra-abdominal abscess 1(4.16%) in OA group and 1(2.04%) in LA group, Bowel obstruction 3(12.5%) in OA group and 2(4.08%) in LA group, Respiratory infection 2(8.33%) in OA group and 1(2.04%) in LA group.Conclusion: This retrospective comparative assessment indicates that the patient chart reduces the incidence of complications in LA was wound infection, intestinal damage, intra-abdominal abscesses, intestinal obstruction and respiratory infections.